PENGARUH PEMBANGUNAN DESA DAN FAKTOR FAKTOR YANG MENGHAMBAT PENGELOLAAN ALOKASI DANA DESA TERHADAP AKUNTABILITAS PUBLIK PENGELOLAAN DANA DESA - Wikan Budi Utami; Ketut Wahyu Ibrahim (ITB AAS INDONESIA, 2019)
Allocation of village founds is financial budget that given to village by government, the source from local tax profit sharing and balanced founds center and local financial received by district. The purpose of this research is determine the effect of village development and factors can be hamper allocation of village founds management on public accountability allocation of village management. The population of this research are villager of Purwosari and the paper uses a sampel are 30 person villager of Purwosari. The sampling technique which is used to get the sample is purposive sampling. Methods of data collection in this research used questionare. Data analysis used descriptive statistical analysis and multiple linier regressions. The data were processed using SPSS 21. The research show that the village development and factors can be hamper allocation of village founds management take effect to publik accountability allocation of village founds management. Keywords: allocation of village founds, village development, factors can be hamper allocation of village founds management, public accountability allocation of village founds management.